Forensic Implications of Saliva: An Overview - Debesh Nilendu1, Arjun Kundu1, Avaish Chand1, Abraham Johnson2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Over past years, investigators and researchers have been repeatedly attracted by possible applications of saliva related evidence in forensics. It is specifically looked for in cases of sexual assault, drug abuse, driving while intoxicated, and in cases involving animal bites. Oral fluid has a role in linking suspects or victims to a crime scene, as well as in profiling of the unknown individual. Collection of salivary evidence should thus be given deserved importance and should be carried out using scientific methods, considering the progression of time, type of case, sequence and type of analytical methods to be performed, nature of surface etc. This review emphasizes the comprehensive use of saliva in forensics.